-9X-6=-X+4

Simple and best practice solution for -9X-6=-X+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9X-6=-X+4 equation:


Simplifying
-9X + -6 = -1X + 4

Reorder the terms:
-6 + -9X = -1X + 4

Reorder the terms:
-6 + -9X = 4 + -1X

Solving
-6 + -9X = 4 + -1X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add 'X' to each side of the equation.
-6 + -9X + X = 4 + -1X + X

Combine like terms: -9X + X = -8X
-6 + -8X = 4 + -1X + X

Combine like terms: -1X + X = 0
-6 + -8X = 4 + 0
-6 + -8X = 4

Add '6' to each side of the equation.
-6 + 6 + -8X = 4 + 6

Combine like terms: -6 + 6 = 0
0 + -8X = 4 + 6
-8X = 4 + 6

Combine like terms: 4 + 6 = 10
-8X = 10

Divide each side by '-8'.
X = -1.25

Simplifying
X = -1.25

See similar equations:

| 0.8(m+2)=0.2(m+26) | | 3x^2+24x+66=0 | | 25=7x-4x+10 | | 1.2-x=0 | | -(x-5)=3 | | 3(5x-9)=4-2 | | 1.2(-4)-0.8x= | | -2d+7-3b=2 | | 3(n+5)=1.5n+11.1-n | | 1.2(-4)-0.8= | | 10x-20=y-2 | | 3y-(x+2)=20 | | 4(5n-6)-7=5n+29 | | 4(8x-8)=-192 | | 7(1-8p)=119 | | 8(x-1)=84 | | -4(3)+2x= | | (x)+(2x+42)=180 | | (4x+1)-4=17 | | 0=2-x | | -8+m+6m=-34 | | -4(1)+2x= | | -4(0)+2x= | | -0.5b-8=-12 | | 1/100(700-200)= | | x-4-5=-17 | | 1/100(800-200)= | | .85a+1.25b=99 | | -4(-2)+2x= | | -8(8a-5)-a=430 | | 5(40)+8y=500 | | 7x-6.2=8x |

Equations solver categories